Pelatihan Dasar Manajemen Bantuan Hidup Dasar (BHD) Karang Taruna Dusun Sribit Dan Sekarsuli, Kapanewon Berbah, Sleman, Yogyakarta - Muhammad Thesa Ghozali; Tiyas Putri Nugraheni; Siti Halimatussa’diyah (Jurnal Surya Masyarakat, 2023)
Basic Life Support (BHD) is very important since it teaches how to provide basic daily life support techniques that are commonly encountered. This community service program intends to provide education as well as training to youth organizations and health cadres of the village who partners with the Community Service Institute of Universitas Muhammadiyah Yogyakarta, namely hamlets of Sribit and Sekarsuli, Berbah, Sleman. The model of the BHD training program was a combination of mini-lecture and practice. Technically, BHD materials were taught by the health professionals to participants 8 times in 1 month. Determination the effectiveness of the program, pretest and posttest were conducted before and after the training. The statistical analysis test results for the total value of the pretest and posttest found that there was an increase in the total of respondents (n=23) who had a good average level of knowledge, from 0 (0%) to 14 (60.8%). The average value of the test also increased, i.e. before the program was 46.13 then became 80.43, with a p value of 0.001 using the Wilcoxon test. This indicated that there is a difference in the respondents’ knowledge before and after conducting basic BHD training. The implication of this program was that the combination of mini lectures and practice could be utilized as an effective approach in providing education and training on BHD for lay people.